The Validity and Reliability of the Turkish Form of the Epilepsy Disclosure Scale—Youth and Parent Versions - Solak, Semen; Kahraman, Ayşe (Journal of Pediatric Epilepsy, 2024)
Although explaining epilepsy is a separate source of stress for children with epilepsy and their parents, studies evaluating the disclosure of epilepsy by patients and their parents are insufficient. The aim of this study was to test the validity and reliability of the Turkish form of the “Epilepsy Disclosure Scale (EDS)—Youth and Parent Versions,” which measures the concealment/disclosure of epilepsy by youth patients with epilepsy and their parents. The population of the study consisted of 126 children who were diagnosed with epilepsy and who were between the ages of 8 to 18 and their parents (63 children and 63 parents) who applied to two hospitals pediatric neurology. Both scales consist of six items. When the scale was adapted, language, content, structural, and reliability analyses were conducted. The factor loads varied between 0.78 and 0.88 and contributed 71.99% to the total variance in the Youth Version. In the Parent Version, they varied between 0.79 and 0.88 and contributed 67.09% to the total variance. The Cronbach's α coefficients of the youth and parent versions of the scale were calculated as 0.92 in the youth version and 0.90 in the parent version. The Composite Reliability Index of the youth version was 0.94, and that of the parent version was 0.92. It was concluded that all statistical studies in the study were compatible with the original scale and that it could be applied to children with epilepsy between the ages of 8 to 18 and their parents in Turkish society.
Keywords: disclosure of epilepsy; children with epilepsy; parents; validity; reliability